2002
DOI: 10.1111/1540-4560.00280
|View full text |Cite
|
Sign up to set email alerts
|

Well–Being Among Older Adults on Different Continents

Abstract: Old age represents a new frontier. The number of older people is increasing throughout the world. This changing demography affects individuals, but also families, communities and societies. The focus of this issue is the well-being of older adults on different continents. Scientists from around the world address this issue using a wide array of research designs and methodologies to provide a broad perspective on aging. Five topics are considered: Well-Being Among Older Adults; Social Support; Functional Statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…Recently, the influence that interactions with family and friends have on maintaining and enhancing older adults' level of physical activity has been the focus of gerontological investigations around the world (Antonucci et al, 2002). Major findings have suggested that support from social networks, including family and friends, leads to increased participation and satisfaction with leisure (Horowitz et al, 1999) and long-term exercise adherence in elderly populations (Cress et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the influence that interactions with family and friends have on maintaining and enhancing older adults' level of physical activity has been the focus of gerontological investigations around the world (Antonucci et al, 2002). Major findings have suggested that support from social networks, including family and friends, leads to increased participation and satisfaction with leisure (Horowitz et al, 1999) and long-term exercise adherence in elderly populations (Cress et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Makoni and Grainger (2002) argue that caregiving should be understood at least in two dimensions: the physical act of caring and helping someone (hands-on care) and the affective state of mind of a person with regard to another, which could be "paraphrased as a 'concern' and sometimes 'love'" (p. 807). They suggest that communication should be perceived as an elemental part of caregiving, and that professional carers should receive training on the relevance of interaction to providing care (Antonucci, Okorodudu, & Akiyama, 2002). These "communication skills" are even more important in contexts of migration, where care-providers and care-recipients may not speak the same language.…”
Section: (Biographical Interview)mentioning
confidence: 99%
“…Its definition varies with the background of the investigator. Sociologists use the term to refer to a person's level of happiness or satisfaction with life, while psychologists define well-being in terms of intrapsychic states such as self-esteem and levels of stress and depression (for an extensive review of the concept of well-being, see, for example, Antonucci, Okorodudu, and Akiyama, 2002;Burroughs and Rindfleisch, 2002;Larson, 1978). Larson (1978, p. 110) points out that within the multiplicity of various and often related definitions and measures of well-being "is a shared core of something that can be called subjective well-being."…”
Section: Differences In Consequences Of Coping Responsesmentioning
confidence: 99%
“…Larson also points out the possible metric inequivalence of common measures of well-being that are based on self reports and the need for caution in comparing scores across ethnic, cohort, and social-class groups, since people in different groups often make different interpretations of the same items of a scale. Because of this limitation, the use of objective measures of well-being such as health is often used along with subjective measures in cross-cultural studies (Antonucci, Okorodudu, and Akiyama, 2002).…”
Section: Differences In Consequences Of Coping Responsesmentioning
confidence: 99%